Russia’s War Against Ukraine: A Contravention of International Humanitarian Law (American Journal of Society and Law, 2023)
In February 2022, Russian forces invaded Ukraine and began targeting military objectives in some major Ukrainian cities. In the following months, airstrikes continued and extended to other areas of Ukraine, including the capital Kyiv. Attacks started being conducted against civilians too. For instance, it has been reported that an apartment complex outside of Kharkiv was directly targeted. International humanitarian law, or the laws of war, protects civilians and noncombatants from the dangers of armed conflict. It addresses the conduct of hostilities-the means and methods of warfare - by all parties to a conflict. Foremost is the rule that parties to a conflict must always distinguish between combatants and civilians. While humanitarian law recognizes that some civilian casualties are inevitable during hostilities, it imposes a duty on parties to the conflict to distinguish between combatants and civilians at all times, and to target only combatants and other military objectives. Civilians lose their immunity from attack when they are “directly participating in the hostilities” - such as by assisting combatants during a battle. This article aimed to contribute to the understanding of the contravention of the international legal framework that regulates the use of force in the Russia - Ukraine armed conflict and how a powerful member of the United Nations Security Council (UNSC) deliberately circumvented treaty provisions on the use of force. The article concludes with a sidebar of the need to exploit avenues for accountability that will help to forestall future occurrences.